(untitled) (International Journal of Engineering and Computer Science, 2018)
Cloud providers like Google, Amazon, Microsoft and IBM have incorporating of Artificial Intelligence capabilities in cloud computing. They provides cloud machine learning platform and artificial intelligence cloud services like computer vision, powerful speech recognition, powerful text analysis, fast dynamic translation, smart search, intelligent language and intelligent knowledge. Artificial Intelligence is a power of new cloud computing generation. In this paper, discuss about artificial intelligence capabilities in cloud computing, in the form of cloud machine learning platforms and artificial intelligence cloud services.